Inhibitory Effect of FMRFamide on NO Production During Immune Defense in Sepiella japonica - Zheng, Libing; Cao, Huimin; Qiu, Jiayin; Chi, Changfeng (Frontiers in Immunology, 2022)
Neuropeptide FMRFamide, specifically exists in invertebrates, plays pivotal roles in various physiological processes. The involvement in neuroendocrine immune regulation was recently reported, and it could modulate nitric oxide (NO) production under immune stress. However, the detailed knowledge was still little known. In this study, we identified Phe-Met-Arg-Phe-NH2 (FMRFamide) as an inhibitory factor on NO in immune reaction of Sepiella japonica. Firstly, Vibrio harveyi incubation caused significantly upregulated expression of FMRFamide precursor and nitric oxide synthase (NOS) in just hatched cuttlefish with qRT-PCR, which indicated that both were likely to be involved in the immune defense. Next, the whole-mount in situ hybridization observed FMRFamide precursor and NOS appeared co-localization, suggesting that FMRFamide might interact with NOS at histological level; NOS mRNA was highly significant upregulated at 72 h when FMRFamide precursor mRNA was knocked down successfully with RNA interference (RNAi) method, which hinted FMRFamide was likely to regulate NO synthesis. Continuously, inflammatory model was constructed in LPS- induced RAW 264.7 cells, FMRFamide administration resulted in highly significant reduction of NO level in dose- and time-dependent manners. Although the adding of iNOS inhibitor (SMT) has inhibited the NO production induced by LPS, the additional FMRFamide could still furtherly sharpen the process. Collectively, it was concluded that neuropeptide FMRFamide could indeed inhibit NO production to serve as feedback regulation in the late stage of immune response to protect hosts from excessive immune cytotoxicity. And the inhibitory effect on NO could not only be mediated by NOS pathway, but it could also be implemented through other pathways needed to be furtherly explored.